The possibility of reducing the risk of developing preeclampsia (review of foreign literature) - S A Levakov; E I Borovkova; N A Sheshukova (IP Berlin A.V., 2015)
The article presents a review of international literature on the possibilities of prevention of pre-eclampsia in women at high risk. Given data from recent randomized trials and meta-analyses, have confirmed whether the use of low-dose antiplatelet therapy with 12 weeks of pregnancy to prevent the development of pre-eclampsia.